Build Career Through Competence: Analysis of the Role of Mediation Employee-Organization Relationship (EOR) in the Manufacturing Industry in East Java - Evi Yulia; Muhammad Imam Syairozi (Sean Institute, 2026)
The purpose of studies This is For know the role of EOR in mediate influence digital competence on success Career . The research method used is quantitative research with a survey method. The population used was employees of a manufacturing company in East Java, with a research sample of 400 employees. The results show that digital competence directly influences EOR and career success. In addition , EOR also influences direct to success career employees . Findings This indicates that EOR does not only own influence directly , but also play role as a mediator in connection between digital competencies and achievements career employees . Implications from studies This give contribution in a way theoretical to development Social Capital Theory , as well as in a way practical offer more insight​ comprehensive regarding strategies that can implemented by the company manufacturing in respond the dynamics of the world of work that continue changed . Besides that , study this also opens opportunity For direction study next more​ deep .